AKUISISI DATA SUMBERDAYA AIR TANAH DI DAERAH SUKODONO KABUPATEN PACITAN - Prayogo, Teguh (Center for Environmental Technology, 2009)
The need of water for human life is very high, especially to meet a demand of water supply, such as for drinking water, washing, taking a bath, and etc. Unfortunately, the availability of surface water at an area is sometimes not enough to comply with a request of pure water, as happened in the Sukodono area. Hence, to avoid the problem, we focus at the ground water sources as alternative water supply. In this paper will be discussed exploration of ground water that is accomplished with imaging resistivity technology to find out characteristic and condition of ground water in Sukodono, Pacitan district, EastJavaProvince. Based on the result of survey in field and interpretation, the existence of aquifer in Sukodono area is occupied between 5 Ã¢â‚¬â€œ 40 meter depth.Ã‚Â Key words : ground water, imaging resistivity, desa Sukodono